Couple relationships and health: the role of the individual’s and the partner’s education - Stauder, Johannes; Rapp, Ingmar; Klein, Thomas (Zeitschrift für Familienforschung, 2019)
Extract-----AbstractA positive correlation between couple relationships and health is well established. However, recent studies indicate that the beneficial effects of couple relationships on health vary substantially according to the characteristics of the relationship and of the partners involved. The present paper examines to what extent partnership effects on physical and mental health differ based on the individual’s education, the partner’s education and educational homogamy between partners. Our database is the German Socio-Economic Panel for the period of 2002 to 2016. Based on fixed effects analysis, our results show that a highly educated partner is more beneficial for mental and physical health than a partner with low education. In contrast, the effects of partnerships on health do not depend on whether the partners have same or different educational levels. The results also indicate that partnership effects on health depend on mate choice and on the potential to find a highly educated partner. Education-specific partnership effects on mental health are more prevalent for women, and effects on physical health are more prevalent for men.Key words: mental health, physical health, couple relationship, partnership, cohabitation, marriage, education, partner’s education, homogamy, educational homogamy-----Paarbeziehungen und Gesundheit: Die Rolle der Bildung des Individuums und seines PartnersZusammenfassungEin positiver Zusammenhang zwischen Partnerschaft und Gesundheit ist lange bekannt. Neuere Studien zeigen jedoch, dass die Gesundheitseffekte von Paarbeziehungen von den Eigenschaften der Beziehung und den Eigenschaften der Partner abhängen. Der Beitrag untersucht, ob und inwieweit die Einflüsse einer Paarbeziehung auf die physische und die mentale Gesundheit vom Bildungsniveau des Individuums, dem seines Partners und von der Bildungshomogamie abhängen. Mithilfe von Fixed-Effects-Modellen werden Daten des Sozioökonomischen Panels (SOEP, Wellen 2002-2016) analysiert. Die Ergebnisse zeigen, dass ein Partner mit hoher Bildung der mentalen und physischen Gesundheit förderlicher ist als ein Partner mit niedriger Bildung. Die Gesundheitseffekte von Paarbeziehungen sind jedoch unabhängig vom Ausmaß der Bildungshomogamie bzw. -heterogamie. Die Ergebnisse weisen darauf hin, dass die Gesundheitseffekte einer Partnerschaft von den Chancen abhängen, einen hoch gebildeten Partner zu finden. Die bildungsabhängigen Partnerschaftseffekte auf die mentale Gesundheit sind stärker bei Frauen ausgeprägt, bildungsabhängige Partnerschaftseffekte auf die physische Gesundheit finden sich dagegen eher bei Männern.Schlagwörter: mentale Gesundheit, physische Gesundheit, Paarbeziehung, Partnerschaft, nicht-eheliche Lebensgemeinschaft, Ehe, Bildung, Bildung des Partners, Homogamie, Bildungshomogamie-----Bibliographie: Stauder, Johannes/Rapp, Ingmar/Klein, Thomas: Couple relationships and health: The role of the individual’s and the partner’s education, ZfF - Zeitschrift für Familienforschung / Journal of Family Research, 2-2019, S. 138-154. https://doi.org/10.3224/zff.v31i2.02
Gesehen am 21.04.2020